2009
DOI: 10.1111/j.1740-0929.2009.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

A fine map for maternal lineage analysis by mitochondrial hypervariable region in 12 Chinese goat breeds

Abstract: As the fast pace of genomic research continues to identify mitochondrial lineages in animals, it has become apparent that many independent studies are needed to support a robust phylogenetic inference. The aim of this study was thus to further characterize the maternal lineage, proposed to originate in southwestern region of China, using a wider survey of diverse goat breeds in China. To this end, we sequenced the mitochondrial hypervariable region 1 (HVR1) of the mtDNA control region in 145 goats of 12 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…Some studies hint that a second independent domestication in Pakistan had given rise to the Cashmere-like goat breeds [1], [34]. However, the question that where is the Chinese goats from, has not been elaborated completely, although there are so many studies focus on it [8], [35], [36], [37]. Phylogenetic analysis of the first hypervariable region of mitochondrial DNA control region had suggested that the goats has multiple maternal origins with a possible center of origin in Aisa, as well as in the Fertile Crescent [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies hint that a second independent domestication in Pakistan had given rise to the Cashmere-like goat breeds [1], [34]. However, the question that where is the Chinese goats from, has not been elaborated completely, although there are so many studies focus on it [8], [35], [36], [37]. Phylogenetic analysis of the first hypervariable region of mitochondrial DNA control region had suggested that the goats has multiple maternal origins with a possible center of origin in Aisa, as well as in the Fertile Crescent [8].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al studied the mtDNA RFLP of 18 native goat populations in China, indicating that the native goat populations in China might originate from two different maternal ancestors [35]. In addition, it was proven that at least one subclade of lineage B was originated from eastern Asia, especially in southwest China [36]. Some studies also support the hypothesis that the southwest of China might be one of the domestication centers [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…The four livestock species were given priority in the domestication course: cattle, pig, sheep and goat (Zeder, 2008). In the fields of domestication history and phylogeography, mitochondrial DNA (mtDNA) has been one of the most preferred markers since it has some advantages such as capacity to demonstrate geographic distribution of species, higher evolutionary rate compared to genomic DNA, maternal inheritance, and absence of recombination (Wu et al, 2009). In comprehensive studies, which are mainly focused on the goat domestication, cytochrome b and Dloop regions located on mtDNA have been frequently used (Luikart et al, 2001; Naderi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The overall ratio of transitions:transversions (40:1) revealed a heavy transition bias in domestic goats. The dloop region variations among four lineages have been reported in previous studies (Wu et al, 2009). …”
Section: Characteristics Of Four Goat Mtdna Lineagesmentioning
confidence: 73%
“…Based on the first hypervariable region of mitochondrial DNA study, 4 samples (one per lineage) were collected and sequenced according to the MJ network of 145 domestic goats (Wu et al, 2009). Fifteen pairs of primers (Appendix Table 1) overlapping in mitochondrial DNA were designed with Premier primer 5.0 and the known goat mtDNA sequence (Parma et al, 2003).…”
Section: Dna Amplification and Sequencingmentioning
confidence: 99%